Ultrasound-involved emerging strategies for controlling foodborne microbial biofilms. (February 2020) - Yu, Hang; Liu, Yang; Li, Lu; Guo, Yahui; Xie, Yunfei; Cheng, Yuliang; Yao, Weirong
Structured abstracts: Background: Pollution of foodborne microbial biofilms is a serious problem in the food industry. Microorganisms in the biofilms become insensitive to environmental stresses and increase tolerance to antimicrobial agents, therefore, making them extremely hard to be inactivated by conventional methods. Ultrasound-involved emerging strategies offer options for effectively controlling the biofilms formed on either food contact surfaces or real foods. Scope and approach: This review emphasizes the significances of either ultrasonication alone or combined with other strategies for controlling foodborne microbial biofilms. Key findings and conclusions: Ultrasound as an emerging technology would effectively destroy biofilm structure and partially inactivate microorganisms in the biofilms; however, stimulated the growth of microbes may happen after treatment of low-frequency and low-intensity ultrasound. Combined ultrasound (especially low-frequency and high-intensity ultrasound) and chemical disinfectants shows a synergistic effect with a relatively high proportion of inactivated microbes in the biofilms compared with that adopted one strategy alone. Ozone and electrolyzed water are also developed for inactivating microbes and removing the biofilms after combining with the ultrasound. Combined treatment of ultrasonication and chelating agents or enzymes is proved to effectively remove the biofilms instead of achieving a strong bactericidal effect. Mechanical oscillation, localized high temperature and pressure, as well as free radicals generated by cavitation during the ultrasonication can partially destroy the basic structure of biofilms, and furthermore, increase the penetration and diffusion of chemicals into the deeper layer of biofilms for achieving a synergistic effect on the biofilm control. Highlights: Ultrasound is used for controlling biofilms formed on foods and food contact surfaces. Combined ultrasound and other strategies show a synergistic effect on biofilm control. Mechanical oscillation and cavitation contribute to destruction of biofilm structure. Bactericidal effect in biofilms depends on intensity and frequency of ultrasound. Future studies are recommended regarding ultrasound-involved emerging strategies.